Diseño y construcción de una planta de detergente en crema con capacidad de 5000 ton/año - Méndez, J. (2009)
The information presented in this article, is based in a manual way process which we tray to industrialize. The objective of this article is to present the bases and certain technical approaches for the design a Plant of Cream Detergent; for such an effect leaves with the definition of the production process, and stops later on to determine the machines, teams and other facilities that it will be required to manufacture this new product. The plant design calculations, specifically the related to the capacity is carried out in function of the dear projections of sales that are hoped to get. The structural calculations and of mechanical facilities they will be based on accepted norms of design. The cost of the project is presented, as well as they are carried out calculations of the cost of outburst of the plant and the cost of monthly operation. At the end of this work it is expected to have presented the guides for the design of plants for production of this type.